(untitled) (Medico Legal Update, 2021)
As a teaching of the Dignified Justice Philosophy, that the purpose of the law is to humanize human being, Legal Aid for patients, especially patients who come from socially marginalized and the poor people who are the victims of medical malpractice in the legal relationship of health services have become the legal norm in the Pancasila Legal System. Using a normative legal research method this research has found that Legal Aid is essentially the manifestation of the institution of justice. This legal institution is provided for the legal relationship of the medical-legal service has been considered as a dignified legal protection model. Since, in this legal institution the position of patients as consumers especially the poor and marginalized patients as consumers of health services who happened to be the victims of medical malpractice are made equal with doctors and nurses and hospitals in the health services. As the institution of the law, the dignified Legal Aid makes it possible for patients especially patients from the poor and marginalized society could afford justice and managed in helping those who did medical malpractice being held accountable before the law, including before the criminal court after being held ethically accountable in the court of ethics.